IDENTITY BASED CRYPTOGRAPHY FOR MOBILE AD HOC NETWORKS - Narayana, V Lakshman; Bharathi, C R (Journal of Theoretical and Applied Information Technology, 2017)
MANETs (Mobile Ad Hoc Networks) are facing the common problems in providing security in all aspects. Their natural characteristics make them vulnerable to passive and active attacks, in which misbehaving nodes can eavesdrop or delete packets, modify packet contents. The Identity-based cryptography system to MANET mainly concentrates on deal out the responsibility of consistent ability among the multiple nodes in a network. Cryptographic technique which uses public key is the mechanism considered in this regard. Secret sharing mechanism is adopted by many existing systems which involves secret sharing of keys to a trusted node among nodes in a network which increases security level. Here we propose threshold cryptography which makes the authority more robust against network disasters and harder to negotiation. Identity-based cryptography, where any identity may assist as a public key, makes certificates and certificate distribution superfluous. The authority distributing private keys corresponding to identities is called a Private Key Generator (PKG). The proposed method deliberates distributing a PKG towards the nodes in the MANET. It shows the security properties of the base IBC systems are preserved when this distributed PKG is used instead of the original.